Alimentador automático para animais utilizando Arduino - Santos, Bruno Feu de Brito [UNESP] (2015)
This paper presents a Project of an automatic feeder for pets using an Arduino Uno as the control center. Through studies on this driver was possible to create a device with an interface capable to receiving user input and then use it to activate the feeder in the defined hours. For mounting equipment were used steps motors, sensors, keyboard and display, which work together to instrument operation. The project goal was reached and the prototype developed indicating that the Arduino can be used for various applications that can simplify daily tasks